Management of Urban Air Logistics with Unmanned Aerial Vehicles - Silva, Mário André Pinto e (2022)
The evolution of the urban environment has changed significantly in the last 50 years, and we see considerable investments in urban logistics in order to make urban processes more efficient. This investigation intends to study the situation of urban logistics with the objective to study the current state of this system and analyze what lies ahead in the near future. The unmanned aerial vehicle (UAV) has been under investigation in the world of logistics, having been pointed has the next logistic technology. For that reason, we set as an objective, analyze the working process of this aircraft, its capabilities, and its limitations. Based on this information, we intend to implement a scenario of deliveries in an urban environment. This scenario will be in the city of Aveiro and consists on the delivery of medicines into pharmacies located in an urban environment. With this study, we pretend to find the best current and future solution to operate in an urban environment. The study is divided into several studies, starting with an analysis of the literature, and then we carry out the SWOT analysis. Then we implement a delivery route to pharmacies, both for daily delivery and emergency medicines. The analysis is divided into two phases, one where the vehicles would initially start from the current logistical base and another phase, where the logistical base is proposed for a new location, that has been optimized to the delivery route to be carried out. From the various analyzes carried out, we obtain very conclusive results. For routes of significant payload and distance, the UAV is still not able to have great performances, being still preferential the use of a van. However, we verified that for emergency deliveries, the UAV from the new logistics base (L2) would have the best performance, as well as it would be a low cost of implementation. In some results, the performance was close to the van or even better, although it would not be cost effective. For that reason, we foresee a robust competition from the UAV as an emerging technology. It will soon have better capabilities and more competitive prices. The cost reduction of this type of deliveries may soon be possible with the use of UAVs.